2D Hydrogenated graphene-like borophene as a high capacity anode material for improved Li/Na ion batteries: A first principles study. (June 2018) - Makaremi, Meysam; Mortazavi, Bohayra; Singh, Chandra Veer
Abstract: Fast-growing electronics industry and future energy storage needs have encouraged the design of rechargeable batteries with higher storage capacities, and longer life times. In this regard, two-dimensional (2D) materials, specifically boron and carbon nanosheets, have garnered enthusiasm due to their fascinating electronic, optical, mechanical and chemical properties. Recently, a hydrogen boride (HB) nanosheet was successfully fabricated showing remarkable stability and superior physical properties. Motivated by this experimental study, we used first principle electronic structure calculations to study the feasibility of this nanosheet to serve as an anode material for Li/Na/Ca/Mg/Al ion batteries. Most active adsorption sites for single adatoms were evaluated and next adatoms were gradually inserted into the anode surface accordingly. The charge transfer, electronic density of sates, storage capacity, structural stability, open-circuit potential and diffusion energy barriers were explored. Our theoretical study predicts that HB shows outstanding electrode properties for Li and Na ion batteries. The intercalation of both Li and Na adatoms into the HB monolayer can lead to a high identical storage capacity of 1133.8 mAh/g which is promising compared to the capacities of the traditional anode materials; such as graphite (372 mAh/g) and TiO2 (200 mAh/g), and other 2D materials; such as germanene (369 mAh/g), stanene (226 mAh/g), and phosphorene (432.8 mAh/g) nanosheets. These results may open a new horizon for the design of rechargeable batteries with higher storage capacitates.